다이캐스팅용 고열전도도 Al-Zn-Mg-Fe 합금의 특성에 미치는 Zn 및 Mg 첨가량의 영향 - 김기태; Ki Tae Kim; 임영석; Young Suk Lim; 신제식; Je Sik Shin; 고세현; Se Hyun Ko; 김정민; Jeong Min Kim (한국주조공학회지, 2013)
The effects of Zn and Mg amounts on the solidification characteristics, microstructure, thermal conductivity and tensile strength of Al-Zn-Mg-Fe alloys were investigated for the development of high thermal conductivity aluminium alloys for die casting. Zn and Mg amounts in Al-Zn-Mg-Fe alloys had a little effect on the liquidus / solidus temperature, the latent heat for solidification and the fluidity of Al-Zn-Mg-Fe alloys. Thermo-physical modelling of Al-Zn-Mg-Fe alloys by JMatPro program showed MgZn2, AlCuMgZn and Al3Fe phases on microstructure of their alloys. Increase of Zn and Mg amounts in Al-Zn-Mg-Fe alloys resulted in gradual reduction of the thermal conductivity of their alloys. Increase of Mg amounts in Al-2%Zn-Mg-Fe alloys had little effect on the tensile strength of their alloys, but increase of Mg amounts in Al-4%Zn-Mg-Fe alloys resulted in steep increase of the tensile strength of their alloys.